The Role of Electronic Accounting Information Systems in Improving the Quality of Financial Statements: An Exploratory Study in a Sample of Iraqi Commercial Banks in Erbil Governorate - Ramyar Rzgar Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research aimed to identify the role of the electronic accounting information system in improving the quality of financial statements in a sample of Iraqi commercial banks operating in the Erbil governorate. A group of Iraqi commercial banks operating in Erbil governorate, where (100) questionnaires were distributed to the study sample, and (90) questionnaires were recovered by (90%), and (86%) were analyzed by (86%) and the statistical program was used ( SPSS) to analyze data and test hypotheses. The research concluded a set of results, the most important of which are: The use of electronic accounting information systems has a relationship in increasing the quality of the financial statements published by the study sample banks, and it was found that there is an effect of electronic accounting information systems in raising the quality of the financial statements represented by (the basic and enhancing characteristics) of the accounting information contained in these lists. The research came out with several recommendations, the most important of which are: The necessity of keeping pace with developments and pursuing modern systems in the banking sector, training those in charge and working on them by raising their efficiency, and encouraging banks operating in Erbil governorate to train their cadres to use electronic programs and applications. The process of developing electronic accounting information systems is a continuous process in banks and does not stop at the completion of specific stages, due to the continuous development in information technologies and their multiple applications.